M17 Improve accuracy of Chronic Obstructive Pulmonary Disease (COPD) diagnosis by offering quality assured spirometry. (12th November 2015) - Gulati, A; Crocker, C; Carrett, J; Win, T
Abstract : Background and objective: Spirometry is a commonly performed diagnostic test in the primary care with variable quality. Around a quarter of the spirometry done in the community is inaccurate and in up to one half of the cases referred to secondary care, diagnosis is changed when spirometry is repeated. We conducted this study to look at the impact of educational intervention in improving the accuracy of COPD. Methods: Seventeen practices across 2 regions in East of England participated in the study. Nurses from these practices underwent educational intervention in the form of attending a structured training to perform Spirometry. Spirometry data and confidence scores in performing and interpreting procedure were collected pre and post training. Results: Clinician's confidence in performing spirometry improved from 5.1 to 7.6 (p = 0.001) on a visual analogue scale post intervention. Confidence to interpret Spirometry improved from 4.3 to 6.5 (p = 0.001). Following intervention tracing improved in thirty nine percent of patients who had poor quality of tracing pre-intervention. Twenty two percent of patients had a change in diagnosis post intervention with medication changes in 33% of the patients. Conclusions: Educational intervention with a structured spirometry course improves the quality and accuracy of spirometry in the primary care. Study support quality assured spirometry for all healthcare providers who are involved in doing the procedure in primary care.